Quantitative assessment of surface runoff from a catchment area based on hydrological and climatic calculations (Tatta river basin (Yakutia, Russian Federation) case study) - Tusupbekov Zhanbolat A.; Ryapolova Natalia L.; Nadtochiy Victoria S. (Glasnik Srpskog Geografskog Društva)
The calculation of surface runoff from a catchment area has always been of great interest, especially in land use planning and management, designing of water supply facilities, and the assessment of the negative consequences of water. The reliability of the runoff characteristics obtained serves as the foundation for the effective utilization of water resources. The relevance of a quantitative assessment of runoff from a catchment area becomes evident in the context of climate change observed over the past several decades. The analysis of the extent of the impact of climate change on runoff, in conjunction with anthropogenic activity within a stream basin, facilitates the formulation of appropriate water management measures aimed at the effective management of water resources. In order to determine the runoff, in conditions of insufficiently studied hydrological territories, various methods and modeling methods are used. The most representative data can be obtained through methods that consider the primary natural factors, specifically thermal and moisture resources. It is the thermal energy resources and humidification resources along with azonal factors that have a direct impact on the processes of runoff formation. Therefore, the present investigation is dedicated to evaluating the impact of thermal energy elements and surface humidification of the catchment area on the conditions of runoff formation. The novelty of this work lies in the implementation of a genetic method for determining the primary runoff-forming characteristics, based on the joint solution of water and heat balance equations. This methodology provides a more precise determination of runoff characteristics in the absence of hydrological measurements. The outcomes obtained can also be utilized to reveal the capabilities of hydro-technical utilities during their reconstruction.